Manual de crioconservación de embriones de mamíferos domésticos en el laboratorio de la biotecnología de reproducción de la Universidad Técnica de Cotopaxi - Zambonino Bautista, Gabriela Elizabeth (2014)
The reproduction Laboratory in the Veterinary Medicine career at the Technical University of Cotopaxi has equipment for practice under a teacher control and in accordance with the established standards for proper use. The goal of this paper is to develop a manual for embryo cryopreservation pets to be used within the lab in a trust full way. The first chapter contains the introduction literature review about manual for lab development. The second chapter explains the methodology used for the production of manuals, their use places, the necessary resource and the main questions for the lab practices and its annexes. The third chapter covers the manual itself with tips for using the equipment properly according to the university regulations.